Aplikasi Marketplace Pertanian Dan Peternakan (Maritani) Berbasis Android - rizky putra fhonna; Nadia Humaira (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2021)
The Maritani application is an android-based agricultural and livestock marketplace application specifically designed to bring together sellers and buyers on one digitalized platform. The maritime marketplace application aims to facilitate sellers and buyers in buying and selling agricultural and livestock needs as well as food needs online. In its business process, the maritime marketplace application uses the B2C (Business to Customer) business model. Where business activities are carried out by producers to consumers using electronic media directly. The development of the Android-based Maritani marketplace is built with the Flutter framework and uses the Dart programming language. At the time of making the Maritani marketplace application for system development using the waterfall method, the development was started with an analysis of system requirements, then carried out the application display design (Graphic User Interface) implementation stage of the application implementation with the Dart programming language. The result of this research is a market application that can have a positive impact on users, both sellers and buyers. In the Maritani application which has a greater opportunity from the community to share knowledge with other sellers, sellers do not need to be afraid of losing consumers, features and regulations of the online market which greatly affect to increase the credibility and safety of the seller's shop, sellers are not required to have large capital